Pengembangan PAI Melalui Budaya Religius di Sekolah - Alif Achadah (LPPM STAI Ihyaul Ulum Gresik, 2020)
Islamic religious education is one of the most important things in the existence of learning in educational institutions or schools. Religious education should be the basic guideline for all activities that will be carried out on each individual in the social sphere. So that the development of PAI through religious culture in schools is very important and will be a measure of the success of PAI learning process. The religious culture of students must be done to instill behavior that reflects on religion so that religious culture can be carried out and become a habit in social behavior.